Computational fluid dynamics simulation of suspended solids transport in a secondary facultative lagoon used for wastewater treatment (2021)
The facultative lagoon hydrodynamics has been evaluated using computational fluid dynamics tools, however, little progress has been made in describing the transport of suspended solids within these systems, and their effects on fluid hydrodynamics. Traditionally, CFD models have been built using pure water. In this sense, the novelty in this study was to evaluate the influence of suspended solids transport on the hydrodynamics of an facultative lagoon. Two three-dimensional CFD models were developed, a single-phase model (pure water) and a two-phase model (water and suspended solids), for a conventional FL in Ginebra, Valle del Cauca, Colombia. Model results were compared with experimental tracer studies, displaying different tracer dispersion characteristics. Differences in the fluid velocity field were identified when suspended solids were added to the simulation. The fluid velocities in the single-phase model were greater than the fluid velocities obtained in the two-phase model, (0.127 m·s−1 and 0.115 m·s−1, respectively). Additionally, the dispersion number of each model showed that the single-phase model (0.478) exhibited a better behavior of complete mixing reactor than the two-phase model (0.403). These results can be attributed to the effect of the drag and slip forces of the solids on the velocity of the fluid. In conclusion, the fluid of FL in these models is better represented as a two-phase fluid in which the particle–fluid interactions are represented by drag and slip forces.